2001
DOI: 10.1002/j.1875-595x.2001.tb00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Needs and demands for dental care in patients attending the University Dental Hospital in Sri Lanka

Abstract: Normative needs of patients demanding treatment were high and many had demanded treatment before acute symptoms had developed. However, delays in seeking care were evident. Further studies are needed to identify factors for delay in obtaining care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 12 publications
9
54
3
5
Order By: Relevance
“…A study of Nicolas E et al 7 point out 13.5% in France, Moore R et al 16 -10.2% in Denmark, Locker D et al 18 , 16.4% in Canada, Shon W and Ismail AJ 19 of Michigan (USA) -12%. Only the results of 44% reported by of Ekanayake L and Dhamawardena D 13 in Sri Lanka exceed our results. This difference is confi rmed also for the subgroups with high (13-14 points) and very high (15 -20 points) anxiety.…”
Section: Discussioncontrasting
confidence: 91%
“…A study of Nicolas E et al 7 point out 13.5% in France, Moore R et al 16 -10.2% in Denmark, Locker D et al 18 , 16.4% in Canada, Shon W and Ismail AJ 19 of Michigan (USA) -12%. Only the results of 44% reported by of Ekanayake L and Dhamawardena D 13 in Sri Lanka exceed our results. This difference is confi rmed also for the subgroups with high (13-14 points) and very high (15 -20 points) anxiety.…”
Section: Discussioncontrasting
confidence: 91%
“…This result was consistent with the study conducted by Newman and Gift (24), which showed that low income limits consultation of dental services. It is reported that as the education level of individuals increases, oral health care improves, and periodic dental health care consultation becomes more common (25). Richard et al (26) also indicated in their study that educational level is a determinant for periodontal disease.…”
Section: Discussionmentioning
confidence: 96%
“…Assessment of normative needs in patients who seek dental care at an institution is therefore, important as such data could be used to estimate the resources and manpower required to meet the patients. 2,4 Our study shows a statistically significant difference between the felt and normative needs for dental care by the population; this is due to the lack of awareness and attitude of Indian population for oral health care. The normative need was 31.54% more than that of the felt needs of the population.…”
Section: Discussionmentioning
confidence: 74%
“…Normative treatment needs for orthodontic patients depend on the clinical parameters while that of patients' depend solely on the esthetic point; this makes attendance for orthodontic treatment further less. 2 There is also a difference between the felt need (3,681) and utilization of care (3,167), which gives an impression that though people are aware that they have oral health-related problems, still they did not make a point of seeking care. This is due to the fact that nobody considers oral health problems to be fatal; still further prospective studies are needed to identify factors responsible for this neglect for oral health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation